Sensitivity and specificity of fine needle aspiration biopsies performed in patients undergoing thyroidectomy (Research, Society and Development, 2022)
Objective: To identify the sensitivity and specificity of Fine-Needle Aspiration Biopsies (FNAB) performed at Hospital Regional da Asa Norte (HRAN) for the diagnosis of thyroid cancer in patients submitted to thyroidectomy. Methods: This was an observational and analytical study, which analyzed medical records of patients submitted to FNAB at HRAN from April 2015 to December 2021. The data were descriptively analyzed using the SPSS 2.0 program, and using the ROC Curve, considering a p value